The Experiences of Perceiving Social Support from Matrilineal Kinship after Parental Divorce - Hartati, Niken; Minza, Wenty Marina; Yuniarti, Kwartarini Wahyu (International Journal of Psychosocial Rehabilitation, 2020)
An extended family is one source of social support that can help people adjust to psychological distress, such as parental divorce. This article aims to describe the experience of individuals from the Minangkabau ethnicity who have a matrilineal kinship system in getting social support from the extended family of mothers after parental divorce. These objectives will be revealed in three parts, namely the source and form of support, the consequences, and the meaning of support for individuals. This study uses a qualitative phenomenological approach with the interview method as the primary data collection technique involving three participants. The results of the interpretation are strengthened by member checking by the participants. The results showed that the extended maternal family’s social support involved the grandmother and siblings who worked together in providing support. The forms of the supports are quite varied according to needs. The primary support comes from "harta pusaka" (heritage property) in the form of certainty of residence, other assistance related to meeting the financial needs of the divorced families. The presence or absence of social support is very dependent on the quality of relationships between members of the family. The consequences of social support are demands for immediate independence, a sense of hesitation because they have become a family burden, and compliance or conflict. Finally, social support is interpreted as diverse by individuals, which can be explained by the Symbolic Interactionism Theory. This study also provides an additional description of the matrilineal kinship relations in the current Minangkabau society.